A study to evaluate the factors influencing seroma formation after breast cancer surgery at tertiary care centre - P., Suresh B.; G., Sachin H.; Naidu, Madhukar; Gopalkrishna, Varsha (International Surgery Journal, 2018)
Background: In the world, breast cancer is the most prevalent malignancy affecting women and stands second in cancer related deaths amongst women. Surgical intervention remains the main stay of treatment. Seroma formation is one of the predominant complications of breast cancer surgery, the cause remaining obscure and with multiple casual provenience. In view of this, we collected data to determine the factors related to incidence of seroma formation in our patients and increase its scope and hence attempt to contravene it. Methods: A retrospective study of 83 carcinoma breast patients who underwent breast cancer surgery from 1st January 2014 to 31st August 2018. Data regarding the following variables compared with age of the patient, BMI, neoadjuvant chemotherapy, tumor size, postoperative exercises/physiotherapy, use of cautery, number of lymph nodes removed, use of closed suction drainage, initial and 72hrs wound drainage. We used chi square and T test methods for statistical analysis of data in our study. Results: The overall seroma formation rate was estimated to be 27%. Factors identified to be significantly related to the formation of seroma are the following: age >45 yrs, tumor size >3cm, number of positive lymph nodes, BMI >30 and total lymph nodes removed, type of surgery. Conclusions: To prevent seroma formation, it is important to identify individual risk factors of seroma formation i.e. the identification of predictive variables which will be vital in designing future trails aimed at reducing the incidence of this common complications of breast cancer surgery.